2010
DOI: 10.2174/1874378101004010152
|View full text |Cite
|
Sign up to set email alerts
|

Water Balance Model of Lake Malawi and its Sensitivity to Climate Change

Abstract: Sustainable water resources development of Malawi needs a thorough assessment of the impact of climate change on the future water levels of Lake Malawi because Lake Malawi together with its outflowing Shire river water system is Malawi's most important water resource for hydropower generation, water supply for industrial and domestic use in the city of Blantyre and its surrounding urban areas together with irrigation water in the Lower Shire Valley (LSV). Any changes in the hydrological or ecological behaviour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…Using the most recent observed climatic parameters of the lake, the predicted level by Neuland (1984) remains below 477 m and further indicated a high probability of negative trend of future water levels as reported in the present study. Kumambala and Ervine (2010) further added that it is very unlikely for the water level to increase to a maximum height of 477 m as it was in 1980. Recent prediction by Kaunda (2015) indicated that near future and far future projects show that water yield will decrease by 8.84% and therefore Lake Malawi water level is expected to drop.…”
Section: Forecastingmentioning
confidence: 99%
“…Using the most recent observed climatic parameters of the lake, the predicted level by Neuland (1984) remains below 477 m and further indicated a high probability of negative trend of future water levels as reported in the present study. Kumambala and Ervine (2010) further added that it is very unlikely for the water level to increase to a maximum height of 477 m as it was in 1980. Recent prediction by Kaunda (2015) indicated that near future and far future projects show that water yield will decrease by 8.84% and therefore Lake Malawi water level is expected to drop.…”
Section: Forecastingmentioning
confidence: 99%
“…Previous hydrological studies have assessed the trends and relationships between the water level in Lake Malawi [44,45], the discharge in the Shire River [46], and the observed and potential impacts of climate change on the local hydrology [47,48] and hydropower generation [49], as well as the perceived risks and potential adaptation options under climatic and socio-economic uncertainty in the Shire River Basin [50]. The literature has also highlighted that the lake level is highly sensitive to climate variability [46], with cyclic fluctuations in levels being largely subject to annual rainfall patterns and seasonal precipitation and temperature variables anticipating lake level changes by approximately two months.…”
Section: Introductionmentioning
confidence: 99%
“…The literature has also highlighted that the lake level is highly sensitive to climate variability [46], with cyclic fluctuations in levels being largely subject to annual rainfall patterns and seasonal precipitation and temperature variables anticipating lake level changes by approximately two months. According to modelling studies based on downscaled climate projections [48], a warmer climate will likely contribute to a further decrease in the water balance. Concerning discharge in the Shire River, local precipitations and temperature have been found to anticipate river flow surges by 2 d [46].…”
Section: Introductionmentioning
confidence: 99%
“…S1), is the third largest of the African Great Lakes and ninth in the world, with an area of 29 600 km 2 , a maximum width of 75 km, and a maximum length of 560 km. Lake Malawi is an important water resource for surrounding tropical southeastern African nations such as Malawi, Mozambique, and Tanzania (Kumambala and Ervine, 2010). In particular, a large part of agriculture and energy in Malawi originates from the water resource of Lake Malawi and the Shire River which flows from the lake; all of the national hydropower stations are built on the Shire River (a total installation capacity of 280 MW; Kumambala and Ervine, 2010) and the largest national sugar plantations are supplied with water from the Shire River.…”
Section: Introductionmentioning
confidence: 99%